Dados abertos: desafios e oportunidades - Flausino, Maiara Guimarães (2024)
The data opening movement has been a strategy used by the public administration to allow community engagement in the search for solutions for the city. Data is considered open when it is available for access, use and sharing by anyone, without restrictions, except those necessary to preserve its origin and open nature. In this direction, this work presents a Systematic Mapping of Literature (MSL), aiming to identify the main challenges related to the provision of open data. Furthermore, different perspectives and motivations associated with these challenges were addressed, as well as a case study, using three Brazilian Open Data Portals.